(untitled) (Global Journal of Human-Social Science, 1970)
The abstract outlines the content of a review on Math Modules a program designed to facilitate the learning of foundational math skills through cognitive training techniques that are based on theory with a special focus on planning and executive functions encompassing cognitive flexibility attentional control and working memory The guiding educational principle is drawn from Vygotsky s concept of zones of proximal development highlighting the belief that children can accomplish tasks with assistance that they may struggle with independently In a way the structure of cognitive training Modules can be viewed as an attempt at construct validity A review of historical roots of Math modules is presented at some length The program begins with the division of training the two key components of math proficiency computing and solving word problems Both rely on five essential skills A specific module on working memory training is cited as an illustrative example of Vygotsky s teaching method A subsequent section summarizes two empirical research studies shedding light on the effectiveness of Math Module training Towards the conclusion the review acknowledges its limitations notably the absence of a comprehensive review of contemporary publications on math cognition and the need for more studies assessing the efficacy of Math Modules The concluding remarks reflect on the concept of validity juxtaposing the number of empirical studies provided with the validation of the construct rooted in Vygotsky and Luria s brain-based research The abstract tangentially touches upon the limits of empirical testimony in the context of the discussed research